8-(Biphenyl-2-yl)-7,9-diphenyl-8H-cyclopenta[a]acenaphthylen-8-ol - Jones, Peter G. (International Union of Crystallography, 2009)
In the title compound, C(39)H(26)O, the cyclopenta[a]acenaphthylene skeleton displays the expected distortions, with formal sp (2) bond angles as high as C—C—C = 142.50 (10)°. The OH group forms intermolecular hydrogen bonds via x-axis translation to the centroid (Cg) of the pendant phenyl ring of the biphenyl system, with H⋯Cg = 2.41 Å and O—H⋯Cg = 153°.